Exploring Chinese Customers Experiences with Chiang Mai Guesthouse through Analytical Customer Knowledge Management - Zhang Xiaofan (2020)
© 2020 IEEE. According to the China Tourism Academy, Thailand has become the first choice for Chinese tourists to travel abroad in recent years (2016-2018). Among them, the most obvious change is that nearly 50% of tourists choose to travel independently rather than with group tours. Chinese Free Independent Travelers (FITs) prefer to stay in guesthouses rather than hotels because they want to experience the local culture of Thailand more. However, the data also shows that Thailand is the country in most need the help of FITs. Because there is no guide service during vacation, FITs are faced with a series of problems such as language barrier, transportation, attraction, and conditions of the guesthouse. To promote Chiang Mai local experiences for Chinese FITs so that it can further improve the quality of guesthouse services for Chinese FITs, this paper aimed to identify Chinese customer experiences with Chiang Mai guesthouse service using customer knowledge management (CKM), and Mentoring CoPs. CKM is used to collect the data on customers' basic and expected requirements for the guesthouse in Chiang Mai, while Mentoring CoPs is utilized for building a knowledge learning platform for guesthouse owners to improve the Chinese language performance. The results show that FITs are satisfied with the basic service of the guesthouse, and also hope to further improve the information service to have a better local experience in Chiang Mai.